2006
DOI: 10.3892/ijo.28.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of trypsinogen and tumor-associated trypsin inhibitor (TATI) in bladder cancer

Abstract: Abstract. Tumor-associated trypsin inhibitor (TATI) is a marker of mucinous ovarian carcinoma, but it is also widely expressed in other malignant tumors and normal human tissues. Elevated serum concentrations of TATI are of prognostic value in ovarian, kidney, and bladder cancer. Tumor-associated trypsin is co-expressed with TATI in many malignancies and is thought to be involved in tumor invasion. TATI mRNA has been shown to be overexpressed in bladder cancer. We therefore studied whether trypsinogen expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…An elevated TATI expression has, with few exceptions, been associated with a more aggressive tumour phenotype and poor clinical outcome in several forms of cancer (Paju et al, 2004(Paju et al, , 2007Hotakainen et al, 2006;Lee et al, 2007;Tomlins et al, 2008). Given the frequently observed coexpression of TATI and trypsin in cancer, it can be hypothesised that increased levels of TATI reflect a simultaneous elevation of trypsin and, hence, increased propensity of the tumour cells to invade and spread.…”
Section: P=0079mentioning
confidence: 99%
See 2 more Smart Citations
“…An elevated TATI expression has, with few exceptions, been associated with a more aggressive tumour phenotype and poor clinical outcome in several forms of cancer (Paju et al, 2004(Paju et al, , 2007Hotakainen et al, 2006;Lee et al, 2007;Tomlins et al, 2008). Given the frequently observed coexpression of TATI and trypsin in cancer, it can be hypothesised that increased levels of TATI reflect a simultaneous elevation of trypsin and, hence, increased propensity of the tumour cells to invade and spread.…”
Section: P=0079mentioning
confidence: 99%
“…In vitro, TATI increases cell migration and plays a role in tissue repair (Stenman, 1990). It has been suggested that expression of TATI and trypsin is balanced in normal tissue, but this balance could be disrupted during tumour progression (Hotakainen et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In deed trypsinogens are highly expressed in high grade prostate cancers, and not only by the luminal secretory cells but also by malignant cells, suggesting that trypsinogenes may be involved in promoting tumour growth and invasion [3]. As trypsinogen and TATI have been reported to be co-expressed in a variety of tumours including colorectal [8], ovarian [9] and bladder cancer [10,11] and it had previously been reported that expression of trypsinogens was associated with prostate cancer it seemed logical to investigate the role of TATI in prostate tumours. that trypsinogens and TATI may be involved in prostate cancer invasion and may also be of prognostic significance.…”
Section: J Edwards and Hy Leungmentioning
confidence: 99%
“…8 In other tumors, low expression of SPINK1 is associated with adverse prognosis and aggressive disease, i.e., ventricular and bladder cancer. 9,10 In these tumors, SPINK1 may inhibit tumor invasion by inhibiting protease cascades involving trypsin. Recent studies have revealed another function of SPINK1, i.e., it can promote development and growth of prostate cancer by stimulating the epidermal growth factor receptor (EGFR).…”
mentioning
confidence: 99%